배추에서 Ribosomal DNAs 분포의 비교분자세포유전학적 분석 - Franklin H. Mancia; 김정선(Jung Sun Kim); 황윤정(Yoon-Jung Hwang) (Korean journal of breeding, 2021)
Three Brassica species, namely, Brassica rapa, B. nigra, and B. oleracea are considered economically important as they are grownfor human consumption and biogas production. Like other crops facing agricultural constraints, selective crossing or hybridization in cruciferousvegetables has helped farmers to improve them. This study conducted a comparative evaluation across and within the species through cytogeneticanalysis to provide fresh insights into their chromosome structures and evolutionary relationships. A new karyomorphological parameter confirmedsymmetric karyotypes in all the accessions, thereby allowing for the depiction of the ancestral chromosome karyotype. Several lines of B. rapa, B. nigra, and B. oleracea were subjected to physical mapping using a fluorescence in situ hybridization technique to elucidate thechromosomal distribution of the two types of rDNAs. The signal number and distribution of 18S rDNA across the metaphase chromosomesof B. rapa accessions did not vary as compared to 5S rDNA, which was also observed in several lines of B. nigra. In contrast, the numberand distribution of 5S rDNA loci across the chromosomes in several lines of B. oleracea were found to be more conserved than those correspondingto the 18S rDNA. Overall, this study revealed the evolutionary dynamics of rDNA, which may play an important role in shaping the chromosomekaryotypes of Brassica species. KCI Citation Count: 0